Análise do risco de escorregamentos translacionais em Vitória, ES - Brasil - Effgen, Julia Frederica (2023)
Landslides are part of slopes evolutionary processes present, mainly, on the steepest regions of the planet. In Brazil, due to its hot and humid climate and rugged topography, the South-eastern region is the major landslides-related disasters area, with notable events on the slopes of the Serra do Mar. In Vitória, capital of the Espírito Santo state, the most famous landslide event took place at the Morro do Macaco in 1985, leaving several dead, injured, displaced and houses destroyed. The capital has several landslide susceptibility studies, with predominance on the use of deterministic methods, but few studies related to risk and social vulnerability. Therefore, this thesis aims to analyse the risk imposed to Vitória’s population by landslides. Through the construction of an inventory of occurrences, based on Projeto MAPENCO’s geologicgeotechnical reports made between 1999 and 2017, the shallow landslide typology was identified as the most recurrent. The landslides, generally, are greatly influenced by anthropic processes and ground conditions, and rainfall is the main triggering factor to slope instability. The susceptibility to shallow landslides was calculated through Informative Value, a statistical method. Areas with greater landslide recurrence match with the greater susceptibilities areas, especially on the Central Massif and coastal hills, on the island portion of the municipality, which are steeper, with geotechnical units comprised of rocky outcrops, talus deposits and residual soils and urban land use. On the other hand, lesser susceptibility and recurrence areas are flat, associated to the geotechnical units comprised of beach and fluviomarine sediments. The social vulnerability index was made on a census sector level, with data from the 2010 Demographic Census. The most vulnerable areas are, mostly, on the Central Massif and coastal hills slopes and near mangroves, in poor and needy neighbourhoods, while the less vulnerable areas are located on rich and structured neighbourhoods. The high and very high shallow landslide risk areas are concentrated on the Central Massif and coastal hills, especially on the neighbourhoods most affected by those events. The population exposed to high and very high risks adds up to 18% of the municipality’s total population. They are young, with high dependency ratio, low income and, mostly, black, and brown. On the other hand, low or non-existent risk areas are occupied, mostly, by white, older, richer people with low dependency ratios. Those areas are flat and with no past occurrences registered.